Adaptive natural resource management as a driver of sustainable economic development in Ukraine: Challenges and opportunities - Ludmila Kozak; Mariia Danchuk (University Economic Bulletin, 2024)
The study aimed to analyse the impact of adaptive natural resource management on the sustainable economic development of Ukraine. Specifically, it focused on the challenges the country faces in adapting to changing environmental conditions and the strategies needed to overcome these barriers to ensure efficient resource utilisation. The research explored the role of adaptive management in addressing critical issues such as natural resource depletion, environmental degradation, and climate change, all of which significantly influence Ukraine's economic stability. Key challenges examined included water pollution, soil degradation, atmospheric pollutant emissions, and the environmental consequences of war. The analysis highlighted the potential of adaptive management to enhance the country's economic competitiveness, improve resource efficiency, and foster investment in the "green" economy. The study identified significant barriers to the effective implementation of adaptive strategies, including insufficient data for environmental monitoring, an outdated regulatory framework, and limited involvement of communities and businesses in management processes. Statistical data on water pollution, pollutant emissions, degraded land, and the environmental impact of war provided a basis for assessing the current situation. The findings also revealed opportunities to address these issues through innovative technologies, legislative improvements, and the development of financial mechanisms, such as "green" bonds and grants. The conclusions emphasised that achieving sustainable economic development in Ukraine requires institutional reforms, enhanced monitoring systems, and increased investment in environmental projects. Furthermore, international cooperation and the promotion of educational initiatives were identified as essential components for advancing sustainable development goals
Keywords: 330; ecological sustainability; environmental policy; national security; management strategies; ecosystem services